Karakteristik Pedagang Kaki Lima â€œPasar Tibanâ€ Pada Koridor Pulutan, Jalan Lingkar Salatiga - Yanuasri, Anggita; Sunaryo, Broto (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
The existence of street vendors are often neglected in spatial planning in the region. Though vendors themselves have an important role in supporting the economy. Street vendors grow as a result of job opportunities in the formal sector. Street vendors of pasar tiban on Corridor Pulutan, Ring Road Salatiga grow and develop without planning so that it creates a drag on the performance of the ring road. Therefore, the need to make the arrangement of the space activities of street vendors. While the conduct of spatial activity vendors, please note the characteristics of street vendors in the area. So that it is known that the characteristics of the street vendors of pasar tiban on Corridor Pulutan, Salatiga Ring Road is located and space activities housed in the shoulder and median road on Corridor Pulutan, Salatiga Ring Road, the distribution pattern is linier aglomeration, the nature of the service is not settled, as well as its business activities, the types of merchandise is a food / beverage, clothing, accessories, handicrafts, agricultural products, books, toys, cushions, electronics, grocery, and services / rental. While the commercial vehicle title, tents, carts, tables, cars, motorcycles, bicycles, stalls and shelves as well as a trade every Sunday or public holidays, 05.00 till 10:00 am.